Recollection of Data Logging for Paint Industry - Kanniga , E.; Varma, Akhil (International Journal of Psychosocial Rehabilitation, 2019)
In this project, work focus on a batch Process simulation and Recording the data (Data logging) from the process which can be retrieved for future reference. The process is about the simulation of the Batch process in which the mathematical programming model for optimal scheduling of the operations of a batch processing chemical plant, capable to handle all possible deterministic and many stochastic variations in the set-up and operation times of the batch operations developed previously is applied to operations in a plant of a leading PAINT manufacturer.